2012
DOI: 10.1039/c2np20037f
|View full text |Cite
|
Sign up to set email alerts
|

Natural products from Cephalotaxus sp.: chemical diversity and synthetic aspects

Abstract: The Cephalotaxus genus belongs to the Cephalotaxaceae family of conifers. Over the past decades it has proved to be a fruitful source of interesting natural products, especially alkaloids (cephalotaxine esters) and terpenoids (abietanes, troponoids), which often display medicinal properties, especially in the anticancer area. Homoharringtonine is active against some orphan leukaemia and is nowadays approaching marketability. A phytochemical update will be provided and the total synthesis of alkaloids and terpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
155
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(157 citation statements)
references
References 183 publications
(110 reference statements)
1
155
0
1
Order By: Relevance
“…In a previous study, we showcased the cultivable fungal diversity present in the leaves of Cephalotaxus harringtonia (Knight ex J. Forbes) K. Koch (Langenfeld et al, 2013), an Asian medicinal plant rich in cytotoxic compounds, whose phytochemical content has been particularly well described (Abdelkafi and Nay, 2012;Bocar et al, 2003;Evanno et al, 2008). More than 640 isolates were identified by ITS rDNA sequencing (Langenfeld et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we showcased the cultivable fungal diversity present in the leaves of Cephalotaxus harringtonia (Knight ex J. Forbes) K. Koch (Langenfeld et al, 2013), an Asian medicinal plant rich in cytotoxic compounds, whose phytochemical content has been particularly well described (Abdelkafi and Nay, 2012;Bocar et al, 2003;Evanno et al, 2008). More than 640 isolates were identified by ITS rDNA sequencing (Langenfeld et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of the main plant compounds present in the extracts was thus monitored by mass spectrometry coupled to the XCMS analytical tool (Smith et al, 2006). The chemical identification of these compounds was achieved using the available databases and our knowledge of the C. harringtonia phytochemistry (Bocar et al, 2003;Evanno et al, 2008) (Abdelkafi and Nay, 2012). Their identity was confirmed after isolation from the crude extract and rigorous structural characterization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some 50 alkaloids, falling into two types (cephalotaxine-type and homoerythrine-type) have been isolated and identified from this genus so far [5]. Among these alkaloids, drupangtonine, 11α-hydroxy-homodeoxy-harringtonine, 11β-hydroxy-homodeoxy-harringtonine, 11β-hydroxy-deoxy-harringtonine [6], neoharringtonine, homo-neoharringtonine, (3′S)-hydroxyl-neoharringtonine [7], nordeoxy-harringtonine, homodeoxy-harringtonine and bishomodeoxy-harringtonine have attracted medical interest [8], due to their cytotoxicity against P-388 leukemia cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Research on the biological properties of this alkaloid has shown that HHT inhibits protein biosynthesis in the cell via the breakdown of polyribosomes, the release of completed globin chain, and the inhibition of the initiation of protein synthesis without effecting chain elongation. [4][5] In 2012, omacetaxine mepesuccinate (Synribo), a semisynthetic HHT compound (99.7% purity) was used in studies of chronic myeloid leukemia (CML) and approved by the FDA for the treatment of CML. Later approval from the FDA in 2013 for this drug to be self-administered by patients further demonstrated its efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%